2011 18th Working Conference on Reverse Engineering 2011
DOI: 10.1109/wcre.2011.17
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Dependencies Using Domain information?

Abstract: Abstract-Software dependencies play a vital role in program comprehension, change impact analysis and other software maintenance activities. Traditionally, these activities are supported by source code analysis; however, the source code is sometimes inaccessible, and not all stakeholders have adequate knowledge to perform such analysis. For example, non-technical domain experts and consultants raise most maintenance requests; however, they cannot predict the cost and impact of the requested changes without the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Our domain analysis model is derived from the models proposed by Aryani et al [3], [1], [2]. The three key elements at the domain level are modelled as follows:…”
Section: A Notation and Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our domain analysis model is derived from the models proposed by Aryani et al [3], [1], [2]. The three key elements at the domain level are modelled as follows:…”
Section: A Notation and Definitionsmentioning
confidence: 99%
“…Rugaber [12] showed how domain knowledge can be useful in program comprehension. Given the potentials of domain information, Aryani et al [1], [3] recently showed how domain information can be used to identify dependencies among software components to support change propagation.…”
Section: Threats To Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping domain entities to source code has been used for concept location [26], [27], [25], developing reverse engineering tools [28], [29], and supporting software change process [30]. In a recent work, a coupling metric, termed as domain-based coupling, has been proposed as a method of approximation for software dependencies using solely domain information [31]. We build our approach based on the hypothesis that this metric and the conceptual coupling can complement each other and combining them improves the accuracy of predicting software dependencies.…”
Section: B Domain-based Couplingmentioning
confidence: 99%
“…Conceptual couplings are independent from the underlying programming language or programming paradigm. Likewise, domain-based couplings are derived from the domainlevel relationships embedded in software components, which are independent from software implementation [21]. As such, domain-based coupling can be used to detect dependencies even without access to the source code or the database.…”
Section: Introductionmentioning
confidence: 99%